Desempenho de marcadores de sepse pediátrica e sua relaçâo com a gravidade - Tonial, Cristian Tedesco (2015)
Introduction : Sepsis is a systemic condition of intense inflammation, caused by an infectious agent that serves as the "trigger" of the entire process. Finding tools that allow the healthcare professional to anticipate or accompany an adverse outcome is important in the setting of the Pediatric Intensive Care Unit (PICU). Because of this, several sepsis markers have been studied. The objective of this study is to evaluate the progress and performance of pediatric sepsis markers and their relation with severity. Methods : A prospective cohort study of patients admitted to the PICU of a university hospital from March to December 2014. We included all patients with suspected sepsis who had between 28 days and 18 years, and were requiring mechanical ventilation for more than 48 hours and cardiovascular support by vasoactive drugs. We collected serum levels of C-reactive protein (CRP), ferritin, leukocyte count, triglycerides (TGC), total cholesterol, LDL cholesterol (LDL), growth hormone (GH) and Insulin-like Growth Factor 1 (IGF-1) on the first day (D0), 24 hours (D1) and 72 hours (D3) after recruitment. The Pediatric Index of Mortality 2 (PIM2) was obtained on the first day of admission in the PICU. Patients underwent transthoracic echocardiography to determine the ejection fraction (EF) and shortening fraction (FENC) of the left ventricle on D1 and D3. The outcome measures were length of hospitalization, PICU stay; duration of mechanical ventilation (MV) and ventilator-free hours; duration of use of inotropic and maximum score of inotropic agents; PIM2 and mortality. A value of p < 0.05 was considered significant. Results : During the study period there were 337 hospitalizations. A total of 20 patients completed the study protocol. In terms of demographic, clinical and laboratory characteristics in recruitment, we noted that only ferritin was higher (mean and standard deviation, 454.4 ± 309.7 versus 91.9 ± 6 ng / ml, p = 0.005) in severe patients (PIM2 ≥ 6%). Patients with cardiac dysfunction by echocardiography in D1 had higher hospital stay (p = 0.047), PICU stay (p = 0.020), duration of mechanical ventilation (p = 0.011), maximum inotropic score (p = 0.001), PIM2 (p <0.001) and lower ventilator-free hours (p = 0.020). Patients with elevated ferritin levels in D0 had also less ventilator-free hours (p = 0.046), higher maximum inotropic score (p = 0.009) and PIM2 (p <0.001). The PIM2 differentiated the most severely ill patients by less ventilator-free hours (p = 0.012) and higher maximum inotropic score (p = 0.033). The 2 patients who died during the study had cardiac dysfunction by echocardiography, hyperferritinemia and elevated PIM2. Conclusion : Among the analyzed markers, cardiac dysfunction by echocardiogram (ejection fraction <55% and FENC <28%), ferritin (≥ 300 ng / ml) and (PIM2 ≥ 6%) had the best performance as markers of severity in pediatric patients with sepsis.